TINGKAT EFISIENSI PENAKSIR M TERHADAP PENAKSIR LMS DALAM MENAKSIR KOEFISIEN GARIS REGRESI - Harmi Sugiarti; Andi Megawarni (LPPM Universitas Terbuka, 2010)
The using of OLS method to estimate the regression coefficients in multiple linear regression model presupposed assumption that there is no outlier in the data. Alternatively, robust regression methods can be used. This paper aims to investigate the efficiency of M method and LMS method to estimate the regression coefficients. Besides application data, simulation data generated by MINITAB and SYSTAT package program were used. The investigation shows the LMS method is more efficient than the M method when there is outlier in the data. Otherwise, the M method is more efficient than the LMS method.